2020
DOI: 10.1016/j.foodqual.2020.104033
|View full text |Cite
|
Sign up to set email alerts
|

Long vowel sounds induce expectations of sweet tastes

Abstract: A growing body of research has demonstrated the existence of cross modal correspondences that involve tastes and sounds. For example, front vowels (e.g., /i/) and voiceless consonants (e.g., /f/) are more matched with sweetness than back vowels (e.g., /u/) and voiced consonants (e.g., /b/). However, research on taste-sound correspondences so far has focused mainly on the vowel position (e.g., front vs. back) and/or consonant types (i.e., voiced vs. voiceless). The literature on onomatopoeia and phonaesthetics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Sound symbolism refers to the non-arbitrary mappings that exist between phonetic sounds and their meanings (Knoeferle et al, 2017;Sidhu & Pexman, 2018) and has been shown to be an important factor behind the creation of many of the world's most successful brand names (Abel & Glinert, 2008;Gallace et al, 2011;Klink, 2000Klink, , 2001Klink, , 2003Klink & Athaide, 2012;Klink & Wu, 2014;Spence, 2012Spence, , 2014Velasco et al, 2014). Sound symbolism has also been shown to be effective in altering the consumer perception across various food products (e.g., ice cream, beer), medications (e.g., medicine effectiveness), and even taste attributes (e.g., sweetness, bitterness, creaminess) (e.g., Abel & Glinert, 2008;Klink, 2000;Lowrey & Shrum, 2007;Motoki et al, 2020;Park et al, 2020;Pathak, Calvert, & Motoki, 2020;Yorkston & Menon, 2004). Despite the rich literature published in this field, research linking those sounds contained within a brand name with the perception of healthy food is relatively sparse, and this paper is an attempt to bridge this gap.…”
Section: Sound Symbolism and Brand Namesmentioning
confidence: 99%
“…Sound symbolism refers to the non-arbitrary mappings that exist between phonetic sounds and their meanings (Knoeferle et al, 2017;Sidhu & Pexman, 2018) and has been shown to be an important factor behind the creation of many of the world's most successful brand names (Abel & Glinert, 2008;Gallace et al, 2011;Klink, 2000Klink, , 2001Klink, , 2003Klink & Athaide, 2012;Klink & Wu, 2014;Spence, 2012Spence, , 2014Velasco et al, 2014). Sound symbolism has also been shown to be effective in altering the consumer perception across various food products (e.g., ice cream, beer), medications (e.g., medicine effectiveness), and even taste attributes (e.g., sweetness, bitterness, creaminess) (e.g., Abel & Glinert, 2008;Klink, 2000;Lowrey & Shrum, 2007;Motoki et al, 2020;Park et al, 2020;Pathak, Calvert, & Motoki, 2020;Yorkston & Menon, 2004). Despite the rich literature published in this field, research linking those sounds contained within a brand name with the perception of healthy food is relatively sparse, and this paper is an attempt to bridge this gap.…”
Section: Sound Symbolism and Brand Namesmentioning
confidence: 99%
“…Words which included long vowel(s) increased the perceptual and emotional referents of words which included sound-symbolic words. In fact, Pathak et al reported that words which included long vowels were more associated with sweet food than words which included short vowels [ 57 ]. Another study showed that words which included long vowels negatively correlated with sharpness [ 58 ], although this finding does not suggest that words which included long vowels increased the perceptual and emotional referents of words.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, our findings do not explore the association of odors with individual phonemes (e.g., /i/, /o/). A growing body of evidence suggests that people tend to match individual phonemes with certain food-related attributes Motoki, Saito, Park, et al, 2020b;Pathak et al, 2020Pathak et al, , 2021Yorkston & Menon, 2004).…”
Section: Discussionmentioning
confidence: 99%